FOREIGN LANGUAGE READING ANXIETY AMONG ADVANCED STUDENTS OF ENGLISH – A PILOT STUDY - Marzec-Stawiarska, Małgorzata (Acta Neophilologica, 2013)
The article discusses the problem of foreign language reading anxiety among advanced students of English. It describes a pilot study whose aim was to check whether reading apprehension exists in this group of participants, to investigate cognitive, behavioural and somatic symptoms of anxiety and to create an instrument which would allow for its multidimensional analysis. The study shows that reading anxiety exists at advanced levels of linguistic proficiency. Within cognitive framework of anxiety testing apprehension was found to be prevailing. As far as anxiety generating factors are concerned students are most stressed by inability to understand a text, by activities accompanying reading tasks and by reading aloud. Behavioural and somatic symptoms exist in a small degree in this group of respondents.